A risk‐based multi‐step corrective control method for mitigation of cascading failures - Yumeng Liu; Tao Wang; Xueping Gu (IET Generation, Transmission & Distribution, 2022)
Abstract Minimizing the risk of cascading failures in a power system is vital to balance the operational economy and security. A multi‐step corrective control (MSCC) method is proposed to mitigate cascading effects in terms of reducing risk of blackout by considering the multi‐step propagation characteristics of cascading failures caused by overload. Based on fault chain model and the DC power flow equation, the dynamic interaction between the process of cascading failures and control schemes is first discussed. The corrective control problem is then expressed as a multi‐step decision‐making optimisation problem based on the defined risk indices. The MSCC model with flexibility of control timing is designed by optimizing probability weighting expected cost and overload risk of cascading failure. In this control method, generation re‐scheduling and load shedding are selected as the main remedial actions, and a multi‐layer coding genetic algorithm is employed to obtain the optimal remedial control schemes. The numerical results indicate that control schemes generated by the proposed method could mitigate the cascading failures and result in better performance than non‐recurring corrective control (NCC) in terms of economy and operational risk.